The iron-modulating hormone hepcidin is upregulated and associated with poor survival outcomes in renal clear cell carcinoma - Huang, Jian; Liu, Wang; Song, Shiqi; Li, Jean C.; Gan, Kaimei; Shen, Chunxiao; Holzbeierlein, Jeffrey; Li, Benyi (Frontiers in Pharmacology, 2022)
Background Reliable biomarkers are rare for renal cell carcinoma (RCC) treatment selection. We aimed to discover novel biomarkers for precision medicine. The iron-regulating hormone hepcidin was reportedly increased in RCC patient sera and tissues. However, its potential implication as a prognostic biomarker remains exclusive. Methods Multiple RNA-seq and cDNA microarray datasets were utilized to analyze gene expression profiles. HAMP protein expression was assessed using an ELISA assay in cell culture models. Comparisons of gene expression profiles and patient survival outcomes were conducted using the R package bioinformatics software. Results Five (HAMP, HBS, ISCA2, STEAP2, and STEAP3) out of 71 iron-modulating genes exhibited consistent changes along with tumor stage, lymph node invasion, distal metastasis, tumor cell grade, progression-free interval, overall survival, and disease-specific survival. HAMP upregulation exerted as a superior factor (AUC = 0.911) over the other four genes in distinguishing ccRCC tissue from normal renal tissue. Hepcidin upregulation was tightly associated with its promoter hypomethylation and immune checkpoint factors (PDCD1, LAG3, TIGIT, and CTLA4). Interleukin-34 (IL34) treatment strongly enhanced HAMP expression in renal cancer Caki-1 cells. Patients with higher levels of HAMP expression experienced worse survival outcomes. These data suggest that HAMP upregulation is a potent prognostic factor of poor survival outcomes and a novel immunotherapeutic biomarker for ccRCC patients.